Green Innovation and Total Factor Productivity Relationship: The Case of Türkiye - Dogan, Emrah (Ekonomika, 2025)
In recent years, the global economy has increasingly focused on sustainability and environmental responsibility, and green innovation has emerged as a critical driver of productivity. Therefore, understanding the relationship between green innovation and the Total Factor Productivity (TFP) has gained significant importance. This study aims to empirically examine the relationship between total factor productivity and green innovations in Türkiye from 1998 to 2019, by using the ARDL bounds test. Additionally, the study investigates the effects of foreign direct investments, carbon emissions, financial development, and fixed capital investments on the total factor productivity as control variables. The findings indicate that green innovations have a positive and statistically significant impact on the total factor productivity. Furthermore, the consistency of these results was tested by using the FMOLS estimator, confirming that green innovations positively affect the total factor productivity. The findings of the study provide insights into the potential of green innovation as a driver of productivity growth. The findings contribute to the ongoing discussion on how emerging economies, such as Türkiye, can achieve productivity growth.
Keywords: Green innovation; Total factor productivity; Carbon emissions; ARDL bounds test